Lactiplantibacillusplantarum APsulloc331261 (GTB1™) promotes butyrate production to suppress mucin hypersecretion in a murine allergic airway inflammation model - Kim, Hye-Shin; Kim, Bobae; Holzapfel, Wilhelm H.; Kang, Hyeji (Frontiers in Microbiology, 2024)
Allergic airway diseases are one of the serious health problems in worldwide and allergic airway inflammation is a prerequisite led to the exacerbated situation such as mucus hypersecretion, epithelial barrier damage and microbiota dysbiosis. Because of side effects and low efficiencies of current therapeutics, the need for novel alternatives has been urged. Probiotics in which have diverse and beneficial modulatory effects have been applied to the airway inflammation model and the underlying mechanism needs to be investigated. In our research, we aimed to evaluate whether our target strain, Lactiplantibacillus plantarum APsulloc331261 (GTB1 TM ) isolated from green tea, can ameliorate allergic airway inflammation in mice and to figure out the mechanism. We induced allergic airway inflammation to mice by ovalbumin (OVA) and administered GTB1 orally and the immune and epithelial barrier markers were assessed. The gut metabolite and microbiota were also analysed, and the in vitro cell-line experiment was introduced to confirm the hypothesis of the study. GTB1 ameliorated type 2 inflammation and suppressed mucin hypersecretion with the inhibition of MUC5AC in inflamed mice. Moreover, GTB1 increased the butyrate production and the relative abundance of butyrate producer, Clostridium cluster IV. We assumed that butyrate may have a potential role and investigated the effect of butyrate in mucin regulation via human airway epithelial cell line, A549. Butyrate significantly reduced the gene expression of MUC5AC in A549 cells suggesting its regulatory role in mucus production. Therefore, our study demonstrates that the oral administration of GTB1 can ameliorate allergic airway inflammation and mucin hypersecretion by butyrate production.